Advancements in synthesis, immobilization, characterization, and multifaceted applications of silver nanoparticles: A comprehensive review - Md. Belal Uddin Rabbi; Sadia Haque; Sultana Bedoura (Heliyon)
Silver nanoparticles (AgNPs) have attracted significant interest in recent years owing to their unique physicochemical properties, including antimicrobial reduction capabilities, photocatalytic activity, self-cleaning features, superhydrophobicity, and electrical conductivity. Their characteristics render them highly advantageous for various textile, electronics, food and agriculture, water treatment, and biomedical applications. This detailed analysis explores the recent benefits and drawbacks of various synthesis methods, immobilization techniques, and characterization of AgNPs while emphasizing novel strategies that improve their functionality across different substrates. A comprehensive analysis is conducted on various synthesis methods, including physical, chemical, and biological approaches. Additionally, immobilization techniques such as in-situ synthesis, pad-dry-cure, and printing on diverse substrates are thoroughly examined for their role in enhancing the functionality of textile substrates. Advanced characterization techniques, encompassing spectroscopic and microscopic methods, have been reviewed to provide a comprehensive understanding of AgNPs' structural and functional properties. This review highlights the progress made in synthesizing AgNPs, focusing on the ability to control their size and shape for targeted applications. Improved immobilization methods have significantly enhanced the stability of AgNPs in intricate environments. In contrast, advanced characterization techniques facilitate a more accurate control and assessment of the properties of AgNPs. The utilization of AgNPs as an antimicrobial agent for surface and food protection, medical devices, antiviral agents, and therapeutic tools showcases their extensive influence across the field. The cytotoxic effects of AgNPs on the human body have been thoroughly examined. This review examines recent advancements in AgNPs to encourage additional research and the development of innovative formulations. It also highlights future perspectives and research directions to effectively and sustainably utilize the potential of AgNPs.